2024
DOI: 10.1177/1045389x231221129
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring damage of concrete beams via self-sensing cement mortar coating with carbon nanotube-nano carbon black composite fillers

Liangsheng Qiu,
Linwei Li,
Ashraf Ashour
et al.

Abstract: Self-sensing concrete used in coating form for structural health monitoring of concrete structures has the merits of cost-effectiveness, offering protective effect on structural components, enabling electrical measurements unaffected by steel reinforcement and is also convenient to maintain and replace. This paper investigates the feasibility of using self-sensing cement mortar coating containing carbon nanotube-nano carbon black (CNT-NCB) composite fillers (CNCFs) for damage monitoring of concrete beams. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Wen and Chung [101] obtained a maximum FCR amplitude of 0.15% on the tension side for a 5 mm thick coating with 0.5 wt% added carbon fibre for a beam deflection of about 0.09 mm. The sensing response also agreed with the values defined by Qiu et al [105] (i.e., 2.5%) for CNT-CB mortar coatings on the tension side of elastic bending. Thus, the FCR values in this study are within a broad range of values found in the literature.…”
Section: Electromechanical Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…Wen and Chung [101] obtained a maximum FCR amplitude of 0.15% on the tension side for a 5 mm thick coating with 0.5 wt% added carbon fibre for a beam deflection of about 0.09 mm. The sensing response also agreed with the values defined by Qiu et al [105] (i.e., 2.5%) for CNT-CB mortar coatings on the tension side of elastic bending. Thus, the FCR values in this study are within a broad range of values found in the literature.…”
Section: Electromechanical Testingsupporting
confidence: 89%
“…Existing studies have focused primarily on compressive strain sensing in which the GF ranged between 123 and 490 [90]. A recent work by Qiu et al [105] described the sensing response in specific areas of mortar beams with mixed inclusions of carbon black and carbon nanotubes. They obtained a maximum FCR within the elastic flexural loading of 1.5% in compression and 2.5% in tension, for a filler addition of 2 vol%.…”
Section: Coating Applicationsmentioning
confidence: 99%
“…By correlating variations in electrical features with changes in strain or stress, it becomes possible to detect load redistributions or excessive loading conditions. Similarly, detecting significant changes in electrical conductivity can allow to directly detect cracks and other types of local damages [42,43]. Various suitable fillers are available in both the literature and in the market for this purpose [44][45][46].…”
Section: Smart Shot-earth Concretementioning
confidence: 99%
“…3,4 Anti-corrosion coatings are coverings applied to metal surfaces to isolate them from the surrounding medium and control metal corrosion. Recently, with the introduction of smart materials, smart anti-corrosion coatings with self-healing, 5,6 selfsensing, 7,8 self-cleaning, 9,10 and other functions have emerged. These coatings have significantly extended the service life of coatings.…”
mentioning
confidence: 99%